Penerapan Notifikasi Whatsapp Pada SIMANDI (Sistem Informasi Manajemen Persediaan) Warehouse PT. Buya Barokah Divisi Percetakan Berbasis Web - Sofian, Ahmad; Latifah, Noor; Setiawan, R. Rhoedy (JATISI, 2024)
Background: The use of computerized systems in companies is currently an important prerequisite for all companies, especially trading companies such as PT. Buya Barokah Printing Division. In managing a company to facilitate/support inventory management, it must be supported by a good application system. There is no inventory management system at PT. Buya Barokah, starting from raw materials, ordered finished goods, distribution finished goods, factory supplies and machine spare parts, resulted in an error in valuation that could occur because the data collection was not systematic and was done manually. Aim: This study aims to facilitate the inventory process, so a system is created that allows warehouse managers to search for information, collect information about warehouses, raw materials, finished goods orders, finished goods distribution, factory supplies and machine spare parts. This information system was built using a web-based programming language, namely PHP (Hypertext Preprocessor), with the help of a database, namely MySQL server. Method: The waterfall method is the method used, while the design uses UML (Unified Modeling Language) and ERD (Entity Relationship Diagram). Results: This research will produce a web-based inventory management system equipped with WhatsApp notifications to provide clear and detailed information about existing supplies. Conclusion: The use of Inventory Management Information Systems is very important for companies in increasing efficiency, reducing the possibility of out of stock, increasing productivity, and reducing costs.